Poetry Workshop in the Acute Inpatient Psychiatric Setting: Feasible, Acceptable, and Significantly Beneficial - Thomas-Tran, Jane; Thomas-Tran, Emily Phu; Eisen, Katherine; Kharrazi, Neda; Mason, Daniel (Advances in Social Sciences Research Journal, 2024)
Objective: We investigated the feasibility and acceptability of establishing a therapeutic poetry writing workshop in an acute inpatient psychiatric setting, as well as the impact of participation on measures of mood, hope, and recovery orientation. Methods: Participants were recruited from the inpatient psychiatric units of an academic medical center. As a pre/post measure of effect of the poetry intervention, participants completed the Herth Hope Index (HHI) and the Mental Health Confidence Scale (MHCS) at baseline and follow-up, as well as a Brief Mood Survey (BMS) immediately before and after each instance of participation in the poetry workshop. Student’s t-tests were used to assess for changes on HHI, MHCS, and BMS, as well as to compare the before vs after in these metrics for individuals who attended only one workshop session versus those who attended two or more sessions to assess for dose-dependent effect of the intervention. Workshop participants also optionally completed a satisfaction survey of their qualitative experience of the group. The protocol for leading a workshop is described in detail. Results: There was a statistically significant improvement in multiple subscales of mood according to the pre- and post-measures on the BMS. Results of the HHI indicated a trend toward increased hopefulness. Results of the MHCS showed statistically significant improvement in participants’ confidence in managing day-to-day life with a mental illness. Results of satisfaction surveys indicate that participants had an overwhelmingly positive experience of the group. Conclusions and Implications for Practice: Workshops designed to foster writing and sharing poetry in a group format are likely to be clinically helpful to improve mood for patients in an acute inpatient psychiatric setting. Future research may examine the adaptability of this intervention for outpatient and virtual settings. Impact and Implications: We conducted a poetry workshop for patients in an acute inpatient psychiatric unit. Participation in the workshop even just once provided a statistically significant and clinically meaningful improvement in multiple subscales of mood and confidence in managing day-to-day life with a mental illness. Our study describes in detail the protocol for a mental health clinician to recreate a similar poetry workshop in their own clinic or hospital.